Pengelolaan Supervisi Kunjungan Kelas di SD Negeri 1 Pengkol Grobogan - Waluyo, Eko, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr.Suyatmini,SE.,M.Si (2016)
ABSTRACT Eko Waluyo. Q100140046. Adviser I Prof.Dr.H Abdul Ngalim, M.Hum. Adviser II Dr.Suyatmini, M.Si Management Supervision in Elementary School Classroom Visits 1 Pengkol Grobogan. Thesis University Muhamadiyah Surakarta 2016. This study has three objectives: (1) To describe the planning supervision classroom visits in SD Negeri 1 Pengkol Grobogan, (2) To describe the conduct of supervision visits classes at SD Negeri 1 Pengkol Grobogan, (3) To describe the feedback on the implementation of supervision visits classroom in SD Negeri 1 Grobogan Pengkol. In this study were used as research objects are matters relating to the management supervision in the classroom visits SD Negeri 1 Grobogan Pengkol. This research is a qualitative research. Qualitative research is often referred to as naturalistic research methods for research conducted on natural conditions. There are three methods of data collection in this study: (1) interview, (2) study the documentation, and (3) direct observation. Data were analyzed using four steps: (1) data collection, (2) data reduction, (3) display data or presentation of data, and (4) draw conclusions or verification. Test validity in this study using triangulation techniques. The result showed that planning means used in supervised learning in SD Negeri 1 Grobogan Pengkol form of making learning supervision format used to record what is seen during the implementation of learning systematically as well later as a form of accountability reports . Implementation learning supervision by the principal at SDN 1 Pengkol Grobogan besides supervising aspects of learning itself also discuss the administrative aspects of the class . This is done by the principal on a regular basis with the purpose of monitoring or ongoing supervision . Implementation feedback learning in the supervision of SD Negeri 1 Grobogan Pengkol very important . Because the principal supervisor must be able to create a harmonious relationship and appreciate the personal character and talents of teachers. At the time of invited teachers, principals, teachers must adapt to nature. Keywords: supervision, management, classroom visits